Dermatological manifestations of fungal infection in patients with febrile neutropaenia: A review of the literature. Issue 9 (31st May 2019) - Maddy, Austin J.; Sanchez, Nelson; Shukla, Bhavarth S.; Maderal, Andrea D.
Summary: Febrile neutropaenia (FNP) is a common cause of morbidity and mortality in immunocompromised patients. Although most infections are caused by bacterial pathogens, fungal infections are becoming increasingly more common. Due to its rarity, the diagnosis of fungal infections in febrile neutropenic patients is often delayed. To provide current clinical features, epidemiology, aetiology, diagnosis and treatment of cutaneous involvement of fungal infection in patients with FNP. A retrospective literature review of PubMed was performed, with no language or publishing data restrictions, yielding 116 results. We queried each case for cutaneous lesions associated with fungal pathogens in FNP. We found 54 publications with 215 reported cases of cutaneous manifestations of fungal injury in patients with FNP. This study is limited in that it is a literature review of a disease that is likely underreported. Cutaneous lesions caused by yeasts such as Candida and Trichosporon manifest as diffuse erythematous papules and usually do not develop central necrosis or eschar, while moulds will present as tender nodules that subsequently develop eschar and necrosis. Recognising the cutaneous manifestations of fungal disease can assist in the diagnosis and management of these infections.